Pemanfaatan Pengolahan Metoda Cidat (Circulair Double Anaerobic Tanks) Terhadap Kadar COD, TSS, Ammonia Limbah Cair Industri Pemotongan Ayam - Bambang Suwerda; Heru Subaris Kasjono; Y.B Kamat Kartono (Sanitasi: Jurnal Kesehatan Lingkungan, 2020)
CIDAT method was a waste water treatment plant which was developed to overcome waste water originated from chicken abattoir industry. The method used community-based technology approach, and was developed in Klaci II Village, Margoluwih, Seyegan, Sleman Regency. The research was aimed to study the influence of CIDAT toward the decrease of COD, TSS, and Ammonia concentration in the waste water. The study used “Pre-Test Post-Test With Control Group Design”; and the waste water sampling method was grab sampling of which three repetitions for both the treatment and control groups were conducted. As control group, the Terban chicken waste water installation was chosen. The results showed that the average decrease of COD concentration were from 1855 mg/l to 58,37 mg/l, or 98,85%; TSS: from 1597,5 mg/l to 36,5 mg/l or 97,72%; and Ammonia: from 3,16 mg/l to 0,74 mg/l or 75,81%. This results had fulfilled the corresponding regulation. The study recommend that CIDAT technology can be used to minimize the decrease in environment quality caused by the waste water, and subsequently could protect the health of people living nearby the industry.